MIKROFASIES BATUGAMPING FORMASI BULU DAN KUALITAS BAHAN BAKU SEMEN, PADA LAPANGAN GUNUNG “PAYUNG”, KECAMATAN BOGOREJO, KABUPATEN BLORA JAWA TENGAH - Ajidityo Putro Fadhlillah; Yoga Aribowo; Dian Agus Widiarso (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Bulu Formation is one of formation which is sedimented at Tertiary age in The North East Java Basin. Bulu Formation has a lithological composition of limestones with kalkarenit. Bulu Formation is located in Gandu village, Tahunan Village, and the surrounding areas, District Bogorejo, Blora, Central Java, with a particular study on the